Flexible Ureterorenoscopy versus Semirigid Ureteroscopy for the Treatment of Proximal Ureteral Stones: A Retrospective Comparative Analysis of 124 Patients - Karadag, Mert Ali; Demir, Aslan; Cecen, Kursat; Bagcioglu, Murat; Kocaaslan, Ramazan; Altunrende, Fatih (Urology Journal, 2014)
Purpose: To investigate and compare the stone clearence and complication rates of flexible ureteroscopy (URS) with semirigid URS in patients having proximal ureteral stones. Materials and Methods: The data of 124 patients with proximal ureteral stones who underwent semirigid or flexible ureterorenoscopic lithotripsy between March 2008 and December 2012 were retrospectively investigated. The patients were divided into 2 groups according to the operation types. Group 1 included 63 patients who were treated with semirigid URS and group 2 was consisted from 61 patients who underwent flexible URS. Each group was compared in terms of stone diameter, successful access to the stone, operation time, reoperation rates, stone free status at postoperative 1st and 3rd month and complications. Results: Successful access was achieved in 48/63 (76%) of the cases in group 1 and 57/61 (93%) of the patients in group 2 (P < .05). Initial stone free status was 63.4% (40/63) and 86.8% (53/61) in groups 1 and 2, respectively (P < .05). Third month radiologic investigations revelaed a stone free rate of 77.7% (49/57) in group 1 and 93.4% (57/61) in group 2 (P < .05). Reoperation was required in 20.6% (13/63) of cases in group 1 and this value was only 6% (4/61) in group 2 (P < .05). There was not any statistically significant difference between 2 groups in terms of complication rates (P > .05). Conclusion: Flexible URS is a favorable option for patients having proximal ureteral stones with higher stone free rate; on the other hand semirigid URS seems a less successful alternative for treatment of proximal ureteral stones.